Literatur Review: Faktor-Faktor yang Berhubungan dengan Kualitas Hidup pada Pasien Gagal Ginjal Kronik di Indonesia - Gita Anisa Maulida; Erika Syavira; Nia Fauziah; Risma Akmalia; Ni Wayan Wiwin Asthiningsih (Universitas Muhammadiyah Manado, 2026)
Chronic Kidney Disease (CKD) represents a significant global health challenge, with a trend of steadily rising prevalence, including in Indonesia. Patients with CKD undergoing routine hemodialysis face multidimensional challenges that impact their quality of life. This literature review aims to outline and synthesize factors associated with the quality of life of CKD patients undergoing hemodialysis in Indonesia. A systematic literature review method using the PRISMA approach was employed, involving searches across Google Scholar, PubMed, Garuda, and DOAJ databases. Inclusion criteria covered articles with a cross-sectional analytical observational design involving patients with advanced-stage CKD undergoing hemodialysis, published within the last ten years, and utilizing valid and reliable quality-of-life instruments (WHOQOL-BREF, KDQOL-SF, KDQOL-36). A total of 21 national and international articles were selected through a systematic process, and their methodological quality was assessed via mapping and scoring stages. The results highlight various aspects consistently and strongly associated with the quality of life of CKD patients, including: (1) clinical factors such as the duration of hemodialysis and comorbidities; (2) psychosocial factors such as anxiety, depression, family support, motivation, and fatigue; and (3) sociodemographic factors such as education level and economic status. Depression emerged as the most dominant predictor with the highest odds ratio (OR=10.131), followed by the duration of hemodialysis (OR=8.380) and comorbidities (OR=5.044). It is concluded that the quality of life of CKD patients is multidimensional and influenced by the interaction of clinical, psychological, and social factors. Integrated interventions—encompassing routine psychological screening, the strengthening of family support, and comorbidity management—are essential to improving the quality of life for CKD patients in Indonesia.